Enhanced evaluation of RNA expression in Esophageal Cancer tissues: Combining Microarray and RNA-Sequence approaches - Otto, Nicola Miriam Elizabeth (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.